Asia’s Post-Global Financial Crisis Adjustment: A Model-Based Dynamic Scenario Analysis - Masahiro Kawai; Fan Zhai (Asian Development Review, 2010)
Using a dynamic global general equilibrium model, the paper assesses the short- and medium-term impacts of the global financial crisis for Asian economies and the implications of post-crisis adjustment in East Asia for the world economy. The analysis suggests that East Asia may not be severely hit permanently by the global financial crisis, and that a worldwide fiscal stimulus could play an important role in stabilizing the global economy in crisis. East Asia’s efforts toward strengthening regional and domestic demand, in conjunction with more flexible exchange rate regimes, will promote more balanced regional growth, facilitating an orderly global rebalancing. However, despite the growing size of emerging East Asia in the global economy, the region’s growth rebalancing has only modest spillover effects on the rest of the world. Emerging East Asia can contribute to global growth, but it alone cannot become the sole engine leading post-crisis growth in the world economy.